Physicochemical, Antioxidant and Sensory Evaluation of Dark Chocolate Fortified with Sacha Inchi Powder Roasted at Different Condition - Azhar, Fathiah Nabila Azhar; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
The increasing demand for functional foods had led to a raised interest in fortifying chocolate with nutrient-rich ingredients. This research investigates the enhancement of dark chocolate via the incorporation of sacha inchi powder, a natural source of omega-3 polyunsaturated fatty acids (PUFAs), antioxidants and phenolic compounds. The impact of sacha inchi powder, roasted at two temperatures (T80 and T160) for 15 minutes, was assessed on the physicochemical parameters, antioxidant activity, total phenolic content (TPC) and sensory characteristics of fortified dark chocolate. Sacha inchi powder obtained from Pantai, Negeri Sembilan was added at levels of 3, 5 and 7% (w/w) into melted dark chocolate. The hardness of fortified dark chocolate samples obtained are lower (0.82kg±0.02–1.07kg±0.02) compared to control sample (1.10kg±0.07) with fortification significantly (p